2021
DOI: 10.1101/2021.03.03.433784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of gene content and co-occurrence constrain the evolutionary path toward animal association in CPR bacteria

Abstract: Bacteria from the Candidate Phyla Radiation (CPR) are small, likely episymbiotic organisms found across Earth's ecosystems. Despite their prevalence, the distribution of CPR lineages across habitats and the genomic signatures of transitions amongst these habitats remain unclear. Here, we expand the genome inventory for Absconditabacteria (SR1), Gracilibacteria, and Saccharibacteria (TM7), CPR bacteria known to occur in both animal-associated and environmental microbiomes, and investigate variation in gene cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 114 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…T he recent discovery of the Candidate Phyla Radiation (CPR), a large monophyletic radiation of phyla and superphyla that includes the group currently referred to as Patescibacteria (1) and accounts for over 26% of microbial diversity, has greatly expanded the bacterial tree of life (2)(3)(4). Among the CPR (>73 phyla), Saccharibacteria (formerly known as TM7) represents one of the only three phyla, the other two being uncultivated Candidatus Absconditabacteria and Candidatus Gracilibacteria, whose members are detected in mammalian microbiomes in addition to diverse environmental niches (5,6). Analyses suggest multiple acquisition events (transfer of bacteria from the environment to mammals that results in stable incorporation into the mammalian microbiome) in the past led to the current wide diversity, with convergent evolution of key functions allowing Saccharibacteria from the environment with already extremely reduced genomes to adapt to mammals (7).…”
mentioning
confidence: 99%
“…T he recent discovery of the Candidate Phyla Radiation (CPR), a large monophyletic radiation of phyla and superphyla that includes the group currently referred to as Patescibacteria (1) and accounts for over 26% of microbial diversity, has greatly expanded the bacterial tree of life (2)(3)(4). Among the CPR (>73 phyla), Saccharibacteria (formerly known as TM7) represents one of the only three phyla, the other two being uncultivated Candidatus Absconditabacteria and Candidatus Gracilibacteria, whose members are detected in mammalian microbiomes in addition to diverse environmental niches (5,6). Analyses suggest multiple acquisition events (transfer of bacteria from the environment to mammals that results in stable incorporation into the mammalian microbiome) in the past led to the current wide diversity, with convergent evolution of key functions allowing Saccharibacteria from the environment with already extremely reduced genomes to adapt to mammals (7).…”
mentioning
confidence: 99%
“…A total of 1326 CPR genomes (1032 GTDB representative genomes, 282 freshwater CPR assembles in this study, 12 MAGs obtained by Jaffe et al [79]) were screened for the presence of rhodopsins. We were able to detect 115 rhodopsin sequences in 86 genomes, out of which 17 were predicted to be protonpumping rhodopsins while the rest had a reverse orientation (N-terminal in the inside, C-terminal in the outside of the membrane [80]) and were therefore inferred to be heliorhodopsins (HeRs).…”
Section: Rhodopsins Occurrence In Cprsmentioning
confidence: 99%
“…Type I rhodopsin [100] can generate a PMF or ion gradient, which could be used for energy production. As some Saccharimonadia MAGs obtained from freshwater lake samples in Sweden and Finland, as well as from glacial surface ice in Greenland [79] encoded genes annotated with low con dence as bacteriorhodopsin, it was hypothesized that they might encode protein pumping rhodopsins (Supplementary Table S15). Bins that were investigated by Jaffe et al [79] form a freshwater cluster in our rhodopsin phylogeny in between Sensory Rhodopsin I (SRI) and II (SRII) (Figure 7), but we were unable to nd any of the proteins involved in the signal transduction from SRI/II in the near genome context [101,102] (Supplementary Figure S17).…”
Section: Putative Rhodopsins Roles In Cprsmentioning
confidence: 99%
“…Recent studies on microbial diversity in human and environmental samples based on whole metagenomics analyses has made it possible to identify a new group of microorganisms that are not well recognised by the 16S rRNA gene, and which continue to be resistant to culture: the Saccharibacteria or TM7, is the most studied CPR phylum and was named due to its sugar metabolism (17). Sequences belonging to this phylum have been systematically detected in several environmental and ecological samples, including soil, freshwater lakes, dolphin teeth, and termite guts (18,19). In addition, metagenomics studies have shown that members of TM7 are also present in the human microbiome, including the intestinal, oral, urinary, cutaneous, blood and vaginal microbiota (11,17,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Saccharibacteria or TM7, is the most studied CPR phylum and was named due to its sugar metabolism (17). Sequences belonging to this phylum have been systematically detected in several environmental and ecological samples, including soil, freshwater lakes, dolphin teeth, and termite guts (18,19). In addition, metagenomics studies have shown that members of TM7 are also present in the human microbiome, including the intestinal, oral, urinary, cutaneous, blood and vaginal microbiota (11,17,(20)(21)(22).…”
mentioning
confidence: 99%